1986
DOI: 10.1677/joe.0.1110137
|View full text |Cite
|
Sign up to set email alerts
|

Episodic prolactin and growth hormone secretion not related to the actual suckling activity in lactating rats

Abstract: In order to characterize the secretion pattern of prolactin and GH in freely behaving lactating rats, frequent serial blood samples were collected through indwelling atrial cannulae and their prolactin and GH concentrations determined by radioimmunoassay. At the time of blood sampling, physical contact with the pups was recorded. Plasma prolactin and GH levels showed episodic changes which were independent of each other and there was no apparent correlation between hormone levels and contact between mother and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Prolactin levels were within the range reported for lactating animals and showed the characteristic dechne as a function of lac¬ tational age (Mattheij et al 1984). In agreement with previous results (Södersten & Eneroth 1984, Nagy et al 1986), we observed no exact concordance between peaks in PRL levels and suckling episodes. There were no significant differences between samphng intervals at any lactational age studied.…”
Section: Resultssupporting
confidence: 89%
“…Prolactin levels were within the range reported for lactating animals and showed the characteristic dechne as a function of lac¬ tational age (Mattheij et al 1984). In agreement with previous results (Södersten & Eneroth 1984, Nagy et al 1986), we observed no exact concordance between peaks in PRL levels and suckling episodes. There were no significant differences between samphng intervals at any lactational age studied.…”
Section: Resultssupporting
confidence: 89%
“…In nonseparated lactating dams whose mammary glands are not engorged because of constant milking activity, only low serum PRL values are observed [9,10]. We carried out experiments both with dams that were not litter deprived and with dams separated from their pups during 4 and 16 h, and we found the highest serum PRL levels in mothers with 16-h separation.…”
Section: Tc # 230mentioning
confidence: 86%
“…However, higher serum PRL levels are not observed in dams that were never litter deprived [9,10], suggesting that other factors besides suckling are involved in enhanced suckling-induced serum PRL levels.…”
Section: Introductionmentioning
confidence: 92%
“…2) [13] in NRS-injected rats. During the 2.5-hour test period, P R L was secreted in one or two bursts.…”
Section: Effect O F Vp-ab and N R S On The Episodic Release O F P R Lmentioning
confidence: 92%